04 The regulation of mitochondrial energy metabolism by L-carnitine lowering agents in ischaemia-reperfusion injury. Issue 24 (24th November 2011) - Makrecka, M; Kuka, J; Liepinsh, E; Dambrova, M
Abstract : Mitochondrial L-carnitine system plays an important role in energy metabolism of the cardiac cells. Administration of both mildronate and sodium pivalate decreases myocardial concentration of L- carnitine. However, mildronate induces cardioprotective effect, while administration of sodium pivalate results in ventricular dysfunction. The present study was performed to clarify the molecular mechanisms behind the opposite effects of both L-carnitine lowering agents. Mildronate (100 mg/kg) or sodium pivalate (500 mg/kg) were administered to Wistar rats for 14 days to reduce the L-carnitine content in heart tissues to comparable level. In heart tissues, L-carnitine content, activities of carnitine palmitoyltransferase I (CPT I) and carnitine acetyltransferase (CrAT) as well as mitochondrial respiration were measured. In addition, the isolated rat heart ischaemia-reperfusion experiments were performed to analyse the cardioprotective effects of both treatments. The L-carnitine content in heart tissues was decreased after treatment with pivalate (by 55%) and mildronate (by 69%). Pivalate and mildronate reduced CPT I activity by 43% and 19%, respectively. Both treatments decreased the mitochondrial respiration with palmitoyl-coenzyme A by 35% and 27%, respectively. Unlike mildronate, treatment with pivalate significantly decreased CrAT activity and respiration with pyruvate/malate by 28%. Only the treatment with mildronate induced significant reduction in infarct size by 34%. In conclusion, our results demonstrate that mildronate possess anti-infarction activity, but pivalate is devoid of cardioprotective effect due to detrimental effects on mitochondrial energy pathways. The regulation of L-carnitine availability can be used for cardioprotection, but the effects of pharmacological agents on mitochondrial L-carnitine pathways should be carefully monitored.